STRATEGI PBL-GREEN UNTUK MENINGKATKAN LITERASI SAINS, KETERAMPILAN METAKOGNITIF, DAN SIKAP PEDULI LINGKUNGAN PESERTA DIDIK DALAM PEMBELAJARAN BIOLOGI - Kadir, St. Fatima; Muarifah, Muarifah; Muhiddin Palennari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Biology learning in the 21st century faces challenges in enhancing students’ scientific literacy, metacognitive skills, and environmental awareness. Problem-Based Learning (PBL) and the Reading-Questioning-Answering (RQA) strategy have proven effective in empowering cognitive and metacognitive abilities; however, they have not explicitly integrated environmental education and ecolo-gical character formation. This article aims to synthesize relevant literature and introduce an innovative strategy called PBL-GREEN as an extension of PBL-RQA. The method employed is a literature study analyzing national and international journals and books related to PBL, RQA, scientific literacy, metacognition, and environmental education. PBL-GREEN integrates five key stages: Guided Rea-ding, Raising Questions-Answering, Exploring Problems, Environmental Action, and Nurturing Attitudes. This strategy has the potential to enhance scientific literacy through guided scientific reading, foster metacognitive skills through ques-tioning and reflection, and cultivate environmental care through real actions and ecological character development. Therefore, PBL-GREEN offers an integrative approach that connects knowledge, skills, and environment-based learning.